Peso insuficiente ao nascer e crescimento alcançado na idade pré-escolar, por crianças atendidas em creches filantrópicas do município de Santo André, São Paulo, Brasil Insufficient weight at birth and preschool-age growth in children attending charitably funded crèches in the municipality of Santo André , in the State of São Paulo , Brazil - Renato Minoru Yamamoto; Denise de Oliveira Schoeps; Luiz Carlos de Abreu; Claudio Leone (Instituto Materno Infantil de Pernambuco, 2009)
OBJETIVOS: comparar o crescimento alcançado e a prevalência de baixa estatura na idade pré-escolar entre recém-nascidos de peso insuficiente (PNI) e de peso adequado (PNA). MÉTODOS: foram estudadas 323 crianças com PNI e 886 com PNA de famílias de baixa renda de quinze creches filantrópicas de Santo André, São Paulo, Brasil, em 2001 e 2002. As variáveis foram o escore Z de peso e de estatura para a idade, pelo referencial Center for Disease Control (CDC) and National Center for Health Statistics (NCHS) 2000, comparando-se as médias dos dois grupos. Calculou-se a razão de prevalência (RP) de baixa estatura na idade pré-escolar em decorrência do peso insuficiente ao nascer. RESULTADOS: o escore z médio de peso foi -0,09 e 0,39 e o escore z médio de estatura foi de -0,06 e de 0,24 para as crianças de PNI e de PNA, respectivamente. A prevalência de baixa estatura foi de 2,78% para as crianças com PNI e de 0,79% para aquelas com PNA. A RP de baixa estatura na idade pré-escolar para as crianças de PNI foi de 3,5 (IC95% 1,3-9,4). CONCLUSÕES: as crianças com PNI apresentaram crescimento inferior e maior risco de falhas de crescimento até a idade pré-escolar, sugerindo um efeito negativo do peso insuficiente ao nascer sobre o crescimento infantil. OBJECTIVES: to compare rate of growth and prevalence of low stature at preschool age in children who were underweight at birth and in children born with a normal weight. METHODS: the study covered 323 children born underweight and 886 born with a normal weight from low-income families in fifteen charitably funded crèches in the municipality of Santo André, in the State of São Paulo, Brazil, in 2001 and 2002. The variables used were the z score for weight and height for age, using the Center for Disease Control (CDC) and National Center for Health Statistics (NCHS) 2000 benchmark, comparing the means for the two groups. The prevalence ratio was calculated for low stature in preschool age children resulting from insufficient weight at birth. RESULTS: the z score for weight was -0.09 and 0.39 and the average z score for height was -0.06 and 0.24 for underweight and normal weight at birth, respectively. The prevalence of low stature was 2.78% for children born underweight and 0.79% for normal weight. The PR for low stature at preschool age for children born underweight was 3.5 (CI95% 1.3-9.4). CONCLUSIONS: children born underweight had a lower rate of growth and greater risk of developing a growth disorder up to preschool age, suggesting a negative effect of insufficient birth weight on child growth.